GaSe-doped polymer microfibre for second-order nonlinear optical processes - Yuxin Ma; Biqiang Jiang; Xiao Xuan; Zhen Hao; Xuetao Gan; Jianlin Zhao (Light: Advanced Manufacturing)
As the most fundamental, efficient frequency-mixing technology, second-order nonlinear optical effects have been extensively applied in the fields of advanced laser technology, microscopic imaging, and optical communication. However, overcoming the limitations of the centrosymmetric nature of traditional optical fibres and exciting second-order nonlinearity remains challenging. In this study, we demonstrate a functionally doped polymer microfibre to implement second-order nonlinear processes in an optical fibre system. Few-layer gallium selenide (GaSe) nanosheets with high nonlinear susceptibility χ(2) are doped in polyvinyl alcohol (PVA) to fabricate the hybrid polymer microfibre, which enables strong second harmonic generation (SHG) and sum-frequency generation (SFG) with sub-milliwatt pump power. When pumped by a continuous-wave (CW) laser, the observable SHG signal was excited in the 1500–1630 nm wavelength range, exhibiting a theoretically predicted power dependence. The SFG response was also validated in the GaSe-doped PVA microfibre with the excitation of two CW pumps, with the signal intensity corresponding to the theoretical evolution tendency when the power and wavelength of the pump light were adjusted. Hence, developing GaSe-doped polymer microfibres provides a novel approach toward the fabrication and application of nonlinear optical fibre devices.